The recombinases Rad51 and Dmc1 play distinct roles in DNA break repair and recombination partner choice in the meiosis of Tetrahymena. - Rachel A Howard-Till; Agnieszka Lukaszewicz; Josef Loidl (PLoS Genetics)
Repair of programmed DNA double-strand breaks (DSBs) by meiotic recombination relies on the generation of flanking 3' single-stranded DNA overhangs and their interaction with a homologous double-stranded DNA template. In various common model organisms, the ubiquitous strand exchange protein Rad51 and its meiosis-specific homologue Dmc1 have been implicated in the joint promotion of DNA-strand exchange at meiotic recombination sites. However, the division of labor between these two recombinases is still a puzzle. Using RNAi and gene-disruption experiments, we have studied their roles in meiotic recombination and chromosome pairing in the ciliated protist Tetrahymena as an evolutionarily distant meiotic model. Cytological and electrophoresis-based assays for DSBs revealed that, without Rad51p, DSBs were not repaired. However, in the absence of Dmc1p, efficient Rad51p-dependent repair took place, but crossing over was suppressed. Immunostaining and protein tagging demonstrated that only Dmc1p formed strong DSB-dependent foci on meiotic chromatin, whereas the distribution of Rad51p was diffuse within nuclei. This suggests that meiotic nucleoprotein filaments consist primarily of Dmc1p. Moreover, a proximity ligation assay confirmed that little if any Rad51p forms mixed nucleoprotein filaments with Dmc1p. Dmc1p focus formation was independent of the presence of Rad51p. The absence of Dmc1p did not result in compensatory assembly of Rad51p repair foci, and even artificial DNA damage by UV failed to induce Rad51p foci in meiotic nuclei, while it did so in somatic nuclei within one and the same cell. The observed interhomologue repair deficit in dmc1Δ meiosis is consistent with a requirement for Dmc1p in promoting the homologue as the preferred recombination partner. We propose that relatively short and/or transient Rad51p nucleoprotein filaments are sufficient for intrachromosomal recombination, whereas long nucleoprotein filaments consisting primarily of Dmc1p are required for interhomolog recombination.